2019
DOI: 10.1111/lapo.12118
|View full text |Cite
|
Sign up to set email alerts
|

Dreams Deterred: The Collateral Consequences of Localized Immigration Policies on Undocumented Latinos in Colorado

Abstract: Recent years have seen a broadening of the scope of immigration enforcement. As a result, immigrants free of criminal convictions, once considered low priorities for enforcement, are increasingly subject to arrest, detention, and removal. At the same time, federal immigration authorities have sought the cooperation of states and localities in the enforcement of immigration laws. While there has been growing scholarly attention paid to the ways in which legal geographies can account for variation in local immig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Several respondents described encounters in which they felt as if they were not being treated equally but discriminated against because of their origin and status as asylum seekers. The feeling of being “second‐class citizens” (Lockwood, 1996; see also Abrego & Lakhani, 2015; Martinez & Ortega, 2019) was reflected in continuous implicit accusations questioning the legitimacy of their stay or being denied “a minimum standard of living” (Obinze). Besides security, the need for recognition as equals seemed to be the main driver for the respondents to legalize and leave behind their negatively perceived status as asylum seekers or “tolerated” persons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several respondents described encounters in which they felt as if they were not being treated equally but discriminated against because of their origin and status as asylum seekers. The feeling of being “second‐class citizens” (Lockwood, 1996; see also Abrego & Lakhani, 2015; Martinez & Ortega, 2019) was reflected in continuous implicit accusations questioning the legitimacy of their stay or being denied “a minimum standard of living” (Obinze). Besides security, the need for recognition as equals seemed to be the main driver for the respondents to legalize and leave behind their negatively perceived status as asylum seekers or “tolerated” persons.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, unlike settlement migrants, staying irregularly was not an option for the interviewees because of the perceived negative implications of living in a "legal limbo status" and the persistent, highly undesired possibility of deportation. A recurring theme in all the interviews was how insecurity and an ever-present fear of deportation caused stress and hopelessness (Abrego & Lakhani, 2015;Kraler, 2019;Martinez & Ortega, 2019;Rosenberger & Koppes, 2018;Van Meeteren, 2012). Some interviewees mentioned being subjected to strict travel restrictions and having limited chances for economic upward mobility because specific qualified jobs seemed inaccessible for foreigners in general and asylum seekers in particular: Obinze, who is from Nigeria, describes the jobs asylum seekers can get and stresses "not to push your luck," implying that asylum seekers are "placed" at the lower end of the societal and economic hierarchy and highlighting how insecure legal statuses may function as structural constraints on migrants' agency (Kraler, 2019).…”
Section: Laborization As a Means To Meet Migrants' Aspirations And Needsmentioning
confidence: 99%
“…The enforcement climate today, by increasing immigrants' "deportability" (de Genova 2004), affects the lives of Latina/o immigrants and their communities so profoundly that it is altering long-standing social dynamics, to the detriment of Latina immigrants. An aspect of settlement that gave these women a social advantage and perhaps even a sense of belonging was their ability to forge networks beyond the family to interact with institutions, create community, and advocate for their rights and those of their families (Hondagneu-Sotelo 1994;Martinez 2010;Terriquez 2012). This ability also conferred on Latina immigrants social status because of the social capital they could generate in their communities through their public activities (Menjívar 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Latina immigrants, especially those with children, have been shown to be more likely to tap into these networks because gendered expectations of behavior place them as their families' caretakers (Menjívar 2002). These social ties can aid women with childcare and help them access support services, health care providers, as well as information about their children's education (Menjívar 2000(Menjívar , 2002Delgado-Gaitan 2005;Martinez 2010;Valdez, Padilla, and Valentine 2013). In fact, research has found that after 10 years of US residence, immigrant Latina mothers' participation in their children's schools resembles that of their US-born counterparts (Terriquez 2012).…”
Section: Social Isolation Social Network and The Enforcement Contextmentioning
confidence: 99%
“…Crimmigration is essentially a racial project (also see, Armenta, 2017; Johnson, 2015; Martinez and Ortega, 2018; Provine, 2013; Provine and Doty, 2011) – an ever-expanding system of control that polices and targets immigrants criminalised as ‘illegals’, ‘bogus’ and ‘risky’. It is a set of hostile practices designed to manage/filter out racialised ‘others’ due to their perceived lack of belonging to the (imagined) national community, and involves denigration, punishment and banishment.…”
Section: Managing ‘Undesirable’ Asylum ‘Bodies’: From Safety Net To Pmentioning
confidence: 99%